Soothing the Bereaved: Stylistic-Rhetorical Devices Functioned in English Eulogies - Fadhil Mohammed, Ra'ed; Abbas Lutfi, Narmeen; Lutfi Hussein, Abbas (International Journal of Psychosocial Rehabilitation, 2020)
When encountering with death or loss, people often endeavor to lessen the influence of what they actually want to convey, i.e. to eulogize the loss of a deceased person. To do so, in their eulogies, people resort to certain stylistic-rhetorical devices (such as metonymy, metaphor, mitigation, hedging, mitigation apology expression, and hypophora) to downgrade death and pacify its austerity. In other words, these variations are utilized to make eulogies more expressive and more touching and to help people feel great sense of loss—soothing the agony of death. Thus, this paper intends to shed light upon the use of stylistic-rhetorical devices in eulogies, as they are seen as essential practices in western society manipulated in a burial of a departed person. The data consist of twenty eulogies taken from The Book of Eulogies by Phyllis Theroux / 1997. The study concludes that figurative language (involving stylistic-rhetorical devices: metonymy, metaphor, mitigation with its two types, hedges and mitigation apology expressions, and hypophora) can be powerful in the selected eulogies. Further, these devices are socially developed as mitigation tools to reduce and placate the soreness of death on the bereaved and audience. They provide a more expressive and pleasant revelation of the deceased; i.e. they are identified as adulatory and consolatory strategies for appeasing and calming the feelings and moods of the bereaved.